Local Wisdom in Coffee House Design to Promote Gayo Culture and Tourism (International Journal of Architecture and Urbanism, 2019)
Abstract                            Despite being the fourth largest coffee producing country, Indonesia has low domestic coffee consumption. Recent growing trend of coffee house may help increase the consumption. Gayo Highlands as the origin of a specialty grade coffee may also be benefitted from the growing trend. Coffee house culture in Gayo has also been growing recently. Coffee as the main commodity in Gayo Highlands has influenced the Gayo culture. Coffee culture can help preserve and promote Gayo culture. This paper explains how philosophical design of traditional Gayo architecture as Gayo local wisdom can be adopted into coffee house design in Gayo Highlands. It discusses some elements of traditional Gayo house which can be adopted to the design of Gayonese coffee house. This article shows that the implementation of traditional Gayo house elements such as pÃ«pantarÃ«n, kÃ«rawang and kÃ«lÃ©lÃ©kÃ«n can help preserve Gayo culture and promote cultural tourism.Keywords: Gayo Lut; Coffee House; Architecture